Preface: a special issue on mine reclamation and suitable management for heavy metals - Kwon, H.H.; Shim, Y.S.; Lee, J.; Jang, M.; Kim, K. (2011)
It is our great honor to edit this special issue of Environmental Geochemistry and Health (EGAH), especially with the special theme of mine reclamation and suitable management for heavy metals. This issue has been made up with the extended works of oral or poster presentations that were given at the 2009 International Symposium on Mine Reclamation held cooperatively by the Korea Mine Reclamation Corporation (MIRECO) and the Korean Society for Geosystem Engineering (KSGE) in South Korea. Briefly, MIRECO is a non-profit national corporation that is currently dealing with the most projects of mine reclamation and rehabilitation in South Korea, while KSGE is a society of scientists and technicians who are working on resource engineering and similar fields. At the symposium, more than 60 oral and poster presentations were made by eminent professionals and scholars from across the world, covering several themes such as mine water treatment, soil remediation, treatment and recycling of tailings, ground subsidence, reforestation, risk assessment, GIS, and other mine hazards. Among the presentations, we have carefully selected and are proceeding to publish 17 full papers that follow the discipline of EGAH. This issue holds scientifically excellent works, providing valuable background to study the emerging technology in the field of mine rehabilitation and reclamation as well as proper management for heavy metals.